Bilgi Merkezlerinde Yönetim ı-II - Zarife Yıldırım Mercan (Türk Kütüphaneciliği)
This book prepared by Assoc. Prof. Dr. Erol Yılmaz and Ass. Dr. Leyla Kanık in 2021. The book consists of nine chapters and forty-seven studies. The book, which starts with business-centered management, covers and examines in depth a wide range of topics from information enterprises to information center types and from the management of information centers to the new generation applications in these centers. The book is a guide for researchers and institutions about the management of information centers with the subjects it contains.